ABE providing a low-delay service within best effort. - Hurley, P. (IEEE Network : the magazine of global information exchange)
We propose alternative best effort (ABE), a novel service for IP networks, which idea of providing low-delay at the expense of maybe less throughput. The objective is to retain the simplicity of the original Internet single-class best-effort service while providing low-delay to interactive adaptive applications. With ABE, every best effort packet is marked as either green or blue. Green packets are guaranteed a low bounded delay in every router. In exchange, green packets are more likely to be dropped (or marked using congestion notification) during periods of congestion than blue packets. For every packet, the choice of color is made by the application based on the nature of its traffic and on global traffic conditions. Typically, an interactive application with real-time deadlines, such as audio, will mark most at its packets as green, as long as the network conditions offer large enough throughput. In contrast, an application that transfers binary data such as bulk data transfer will seek to minimize overall transfer time and send blue traffic. We propose router requirements that aim at enforcing benefits for all types of traffic, namely that green traffic achieves low-delay and blue traffic receives at least as much throughput as it would in a flat (legacy) best effort network. ABE is different from differentiated or integrated services in that neither packet color can be said to receive better treatment; thus, flat rate pricing may be maintained, and there is no need for reservations or profiles. We define the ABE service, its requirements, properties, and usage. We discuss the implications of replacing the existing IP best effort service by the ABE service. We propose and analyze an implementation based on a new scheduling method called duplicate scheduling with deadlines. It supports any mixture of TCP, TCP-friendly, and non-TCP-friendly traffic